Architectural composition - Krier, Rob (Edition Axel Menges, 2010)
Rob Krier is a unique voice in today's architectural discourse through his commitment to developing a relevant and pragmatic theory of architecture based on his own experience and observations of architectural practice and opposed to the easy, abstract theorising so common in contemporary architectural writing. Together with his brother Leon, he has perfected a form of presentation in which the potency of his thinking finds its perfect counterpoint in detailed drawings and sketches which argue his case visually through the power of example. Following the success of his widely acclaimend "Urban Space", a work which looked at the problems of our cities from a historical, theoretical and practical standpoint, Krier now applies his particular, highly influential mode of didactic criticism to contemporary architecture in continuing search for fundamental architectural truths